Pengaruh Kepemimpinan dan Budaya Sekolah terhadap Motivasi serta Dampaknya pada Kinerja Guru SMP Negeri di Kecamatan Juli Kabupaten Bireuen - Redha Marta, Muhammad; Iba, Zainuddin (Singkite Journal, 2024)
This teacher performance research examines the magnitude of the important contribution of leadership factors, school culture and motivation as intermediary factors. The case was conducted at a Public Junior High School in Juli District, Bireuen Regency, with a sample of 62 teachers. Using an associative method with a quantitative approach using path analysis. The results found the following: 1) there is a strong causal relationship between leadership and school culture and has a significant influence on motivation and has implications for teacher performance. 2). The leadership factor has a direct and indirect influence on motivation of 24.06% and on performance of 28.62%. 3) The school culture factor has a direct and indirect influence on motivation of 26.52% and on performance of 30.36%. 4) Simultaneously, leadership and school culture contribute to teacher performance, which is 17.25%.